A flexible closed loop supply chain design considering multi-stage manufacturing and queuing based inventory optimization. Issue 10 (2022) - Jahani, Hamed; Gholizadeh, Hadi
Abstract: In this study, a multi-objective nonlinear model is used to design a closed-loop supply chain network. We consider a multi-period, multi-product and multi-stage manufacturing model by employing a queuing system for inventory management of finished and return products under demand uncertainty limitations. The purpose of this paper is to simultaneously reduce the waiting times of queues in warehouses and the costs of production, transportation, inventory and queuing systems. The flexibility of the chain is formulated at three concepts: product flexibility, the flexibility of supply against demand fluctuations, and the flexibility of time to satisfy all demand. The proposed non-linear model is solved by a robust genetic algorithm. A sensitivity analysis of the flexibility ratios reveals several insights for practitioners and academics.